The Role of Self-Confidence and Mood in Shaping Learning Motivation and Academic Achievement: A Study of Senior Students at Islamic Religious Education Program - Kodir, Abdul (Migration Letters, 2023)
This study delves into the challenges faced by senior students enrolled in the Islamic Religious Education Program at the State Islamic University, Sunan Gunung Djati, Bandung. These senior students have exhibited a noticeable decline in their academic performance, evident in the diminishing Cumulative Grade Point Averages (CGPAs). The primary concern voiced by these students centers around a lack of motivation to actively engage in lectures, which is attributed to a less conducive learning environment and a lack of self-confidence in participating actively and constructively during class sessions. This study, which involved 52 senior students enrolled in the Islamic Religious Education Program, employed an online survey as its primary data collection method. The gathered data underwent rigorous analysis using the Statistical Package for the Social Sciences (SPSS) in conjunction with path analysis to derive meaningful insights. The research findings unequivocally reveal that self-confidence (X1) and emotional disposition (X2) play pivotal roles in influencing Academic Achievement (Z). This influence is observed both in direct correlations and through the mediating variable of Learning Motivation (Y). These empirical results underscore the pressing need for the management of the Islamic Religious Education Program at Sunan Gunung Djati State Islamic University, Bandung, to formulate and implement targeted policies. Such policies should be designed to address the challenges faced by senior students, ultimately facilitating their successful graduation with commendable academic achievements.